2014
DOI: 10.1111/gcb.12662
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of coastal ecosystems to changes in harmful algal bloom distribution in response to climate change: projections based on model analysis

Abstract: Harmful algal blooms (HABs), those proliferations of algae that can cause fish kills, contaminate seafood with toxins, form unsightly scums, or detrimentally alter ecosystem function have been increasing in frequency, magnitude, and duration worldwide. Here, using a global modeling approach, we show, for three regions of the globe, the potential effects of nutrient loading and climate change for two HAB genera, pelagic Prorocentrum and Karenia, each with differing physiological characteristics for growth. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(116 citation statements)
references
References 90 publications
1
105
0
1
Order By: Relevance
“…New model results predict that warming of 2.3 • C leads to a 6% reduction in phytoplankton biomass (Chust et al, 2014). Recent work supports the IPCC findings that phytoplankton, including those that cause harmful algal blooms (HABs), are the taxon that has displayed the largest latitudinal range shifts concurrent with climate change, with average distribution shifts of over 400 km decade −1 (Glibert et al, 2014;Poloczanska et al, 2014). In line with the findings of AR5, Calbet et al (2014) observed shifts in microplankton species compositions, suggesting implications for the global carbon pump, as small size cells are likely to be re-mineralized to inorganic carbon at shallower depths.…”
Section: Updates To Ar5mentioning
confidence: 74%
“…New model results predict that warming of 2.3 • C leads to a 6% reduction in phytoplankton biomass (Chust et al, 2014). Recent work supports the IPCC findings that phytoplankton, including those that cause harmful algal blooms (HABs), are the taxon that has displayed the largest latitudinal range shifts concurrent with climate change, with average distribution shifts of over 400 km decade −1 (Glibert et al, 2014;Poloczanska et al, 2014). In line with the findings of AR5, Calbet et al (2014) observed shifts in microplankton species compositions, suggesting implications for the global carbon pump, as small size cells are likely to be re-mineralized to inorganic carbon at shallower depths.…”
Section: Updates To Ar5mentioning
confidence: 74%
“…Future projections indicate a likely expansion of the spatio-temporal window for HAB development (Glibert et al 2014), with causes variously attributed to anthropogenic sources of nutrient input (Smayda 1989, Hallegraeff 1993, Anderson et al 2008, Heisler et al 2008, as well as to changing climatic and oceanographic conditions, including shifts in sea surface temperature, up welling intensity and storm-associated forcing (Bejarano et al 2008, Moore et al 2009, McCabe et al 2016. Along the Iberian Peninsula, large dinoflagellate blooms -previously absent for ~10 yr -are now recurring, as are seasonal diatom/dinoflagellate oscillations comparable to those in the California system (Kudela et al 2005, Trainer et al 2010.…”
Section: Discussionmentioning
confidence: 98%
“…N loads from SGD to nearshore ecosystems have been estimated to be 4 Tg N yr −1 (Voss et al, 2013), and the role of SGD in coastal eutrophication has also been demonstrated (Valiela et al, 1990). These N loads may be an important factor in the development of harmful algal blooms in coastal waters (Anderson et al, 2008;Glibert et al, 2014). Fresh groundwater is often rich in nutrients and other materials from anthropogenic inputs due to coastal development (agriculture, urbanization) (Howarth and Marino, 2006;Null et al, 2012;Rocha et al, 2015), and models predict a 20 % increase in N loads from SGD within the next few decades due to coastal development (Beusen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%